2016
DOI: 10.1093/mnras/stw2242
|View full text |Cite
|
Sign up to set email alerts
|

A possible formation channel for blue hook stars in globular cluster – II. Effects of metallicity, mass ratio, tidal enhancement efficiency and helium abundance

Abstract: Employing tidally enhanced stellar wind, we studied in binaries the effects of metallicity, mass ratio of primary to secondary, tidal enhancement efficiency and helium abundance on the formation of blue hook (BHk) stars in globular clusters (GCs). A total of 28 sets of binary models combined with different input parameters are studied. For each set of binary model, we presented a range of initial orbital periods that is needed to produce BHk stars in binaries. All the binary models could produce BHk stars with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Using MESA, Vos et al (2015) and Lei et al (2015Lei et al ( , 2016 obtained several sdBs with long orbital periods through stable mass transfer or tidally enhanced stellar wind. These sdBs with long orbital periods are also divided into three classes: flash-mixing sdBs, shallow-mixing sdBs, and canonical sdBs.…”
Section: Comparison With Sdbs With Long Orbital Periodsmentioning
confidence: 99%
“…Using MESA, Vos et al (2015) and Lei et al (2015Lei et al ( , 2016 obtained several sdBs with long orbital periods through stable mass transfer or tidally enhanced stellar wind. These sdBs with long orbital periods are also divided into three classes: flash-mixing sdBs, shallow-mixing sdBs, and canonical sdBs.…”
Section: Comparison With Sdbs With Long Orbital Periodsmentioning
confidence: 99%
“…The main deficiency of both scenarios is that they do not explain the physical mechanism behind the enhanced mass loss required on the RGB. Lei et al (2013Lei et al ( , 2015Lei et al ( , 2016 investigated possible mechanisms and showed that if the star is initially part of a wide-binary system (P ∼ 900−4600 d), the mass loss on the RGB can be tidally enhanced sufficiently to delay the helium-flash. Lei et al (2016) estimated that binaries with periods below 1400 d could have survived dynamical encounters during the evolution of ω Cen.…”
Section: Introductionmentioning
confidence: 99%
“…Lei et al (2013Lei et al ( , 2015Lei et al ( , 2016 investigated possible mechanisms and showed that if the star is initially part of a wide-binary system (P ∼ 900−4600 d), the mass loss on the RGB can be tidally enhanced sufficiently to delay the helium-flash. Lei et al (2016) estimated that binaries with periods below 1400 d could have survived dynamical encounters during the evolution of ω Cen. Dynamical encounters could themselves produce tidal stripping through Roche-Lobe overflow (Pasquato et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hot subdwarfs with pulsations can be used for asteroseismic analyses (Charpinet et al 2011). Lei et al (2015Lei et al ( , 2016 used Hot subdwarfs to study the extended horizontal branch morphology of globular clusters.…”
Section: Introductionmentioning
confidence: 99%